Mechanistic Analysis of Physicochemical Cues in Promoting Human Pluripotent Stem Cell Self-Renewal and Metabolism - Hai, Nan (Int J Mol Sci, 2018)
We have previously reported that a porous membrane of polyethylene terephthalate (PET) enables significant augmentation of human pluripotent stem cell (hPSC) proliferation and differentiation. The interaction between hPSCs and the PET surface induces β-catenin-mediated wingless/integrated (Wnt) signaling, leading to upregulation of the expression of adhesion molecules in hPSCs. In this study, we sought to unveil mechanisms underlying the role of the PET membrane in hPSC self-renewal and metabolism. We discovered that physicochemical cues of the PET membrane considerably alter hPSC metabolism by increasing the cell yield and suppressing the generation of toxic byproduct, indicating an effective cell self-renewal and a less apoptotic culture environment in the membrane culture system. Furthermore, we discovered that a caspase-8 medicated apoptotic pathway plays a profound role in obstructing hPSCs grown on a traditional tissue culture plate (TCP). Treating hPSCs seeded on a TCP surface with a caspase-8 inhibitor significantly suppressed cellular apoptotic pathway and improved cell proliferation and metabolism. Our experimental results provided valuable insights into signal pathways influencing hPSC self-renewal during routine maintenance and expansion, which would shed light on large-scale preparation of hPSCs for clinical applications.